Un lugar en el mundo: palabra, saberes musicales e identidad en el Perú del siglo XVII - Véliz Cartagena, Mauricio (2008)
This article examines the representation of musical culture in three Peruvian authors of the seventeenth century. Analysis of their written works highlights the presence and usage of musical knowledge through which these historical actors demonstrate a capacity to construct in writing an individual and collective identity in colonial society.